A Time-Dependent Model Describes Methotrexate Elimination and Supports Dynamic Modification of MRP2/ABCC2 Activity. Issue 2 (April 2017) - Woillard, Jean-Baptiste; Debord, Jean; Benz-de-Bretagne, Isabelle; Saint-Marcoux, Franck; Turlure, Pascal; Girault, Stéphane; Abraham, Julie; Choquet, Sylvain; Marquet, Pierre; Barin-Le Guellec, Chantal
Abstract : Background: Multidrug resistance protein-2 encoded by the ABCC2 gene (MRP2/ ABCC2 ), an efflux transporter expressed at the proximal renal tubule, is rate-limiting for urine excretion of coproporphyrin (UCP) isomers I and III, translating in high UCP [I/(I + III)] ratio in MRP2-deficient patients presenting with the Dubin–Johnson Syndrome. MRP2 is also a major contributor to methotrexate (MTX) clearance. As MTX is both a substrate and an inhibitor of MRP2, time course of the concentrations of MTX in blood could induce functional modification of MRP2 over time, which in turn can modify its own elimination rate. Methods: A 3-parameter time-dependent MTX population pharmacokinetic (PK) model based on a power function accounting for nonlinearity in its clearance was developed using Pmetrics in a first cohort of 41 patients (76 PK profiles) and compared with a previously published 2-compartment model developed with NONMEM and a 3-compartment model developed with ITSIM. In a second cohort (62 patients and 62 PK profiles), the association between the UCP [I/(I + III)] ratio at 3 periods [before MTX administration (P1), at the end of infusion (P2), and at hospital discharge (P3)] and the time-dependent PK parameters of MTX was investigated. Effects of genetic polymorphisms and of coadministered drugs were also studied. Results: The model developed tightly fitted the data in both cohorts. A significant inverse correlation was found between log ( k 1 ) (ie, the rate constant explaining MTX concentration decrease) and the difference in UCP [I/(I + III)] ratio between P3 and P2 (DP3) (β ± SD = −0.025 ± 0.008, P = 0.00443). Conclusions: Self-inhibition of the MRP2-dependent secretion of MTX is a plausible explanation for the time-dependent PKs of this drug. Additional studies specifically designed to evaluate this hypothesis are required. Abstract : Supplemental Digital Content is Available in the Text.